RHINO forms a stoichiometric complex with the 9-1-1 checkpoint clamp and mediates ATR-Chk1 signaling - Lindsey-Boltz, Laura A (Cell Cycle, 2015)
The ATR-Chk1 signaling pathway mediates cellular responses to DNA damage and replication stress and is composed of a number of core factors that are conserved throughout eukaryotic organisms. However, humans and other higher eukaryotic species possess additional factors that are implicated in the regulation of this signaling network but that have not been extensively studied. Here we show that RHINO (for Rad9, Rad1, Hus1 interacting nuclear orphan) forms complexes with both the 9-1-1 checkpoint clamp and TopBP1 in human cells even in the absence of treatments with DNA damaging agents via direct interactions with the Rad9 and Rad1 subunits of the 9-1-1 checkpoint clamp and with the ATR kinase activator TopBP1. The interaction of RHINO with 9-1-1 was of sufficient affinity to allow for the purification of a stable heterotetrameric RHINO-Rad9-Hus1-Rad1 complex in vitro. In human cells, a portion of RHINO localizes to chromatin in the absence of DNA damage, and this association is enriched following UV irradiation. Furthermore, we find that the tethering of a Lac Repressor (LacR)-RHINO fusion protein to LacO repeats in chromatin of mammalian cells induces Chk1 phosphorylation in a Rad9- and Claspin-dependent manner. Lastly, the loss of RHINO partially abrogates ATR-Chk1 signaling following UV irradiation without impacting the interaction of the 9-1-1 clamp with TopBP1 or the loading of 9-1-1 onto chromatin. We conclude that RHINO is a bona fide regulator of ATR-Chk1 signaling in mammalian cells.